2018
DOI: 10.1093/mnras/sty2545
|View full text |Cite
|
Sign up to set email alerts
|

Post-common envelope binary stars, radiative levitation, and blue large-amplitude pulsators

Abstract: Following the recent discovery of a new class of pulsating star, the blue large-amplitude pulsators (BLAPs), pulsation stability analysis was carried out on evolutionary models of post-common envelope (CE) ejection stars of 0.3 and 0.46 solar masses. These models subsequently evolve to become a low-mass helium white dwarf and a core helium-burning extreme horizontal-branch star respectively. We investigate the effects of atomic diffusion, particularly radiative levitation, on the pulsation behaviour of the mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
5
23
0
Order By: Relevance
“…We have found a new class of radial mode pulsators (high-gravity-BLAPs) with T eff ≈ 30, 000 K that are consistent with ≈ 0.25 − 0.3 M ⊙ low-mass He-core pre-WDs transiting the newly identified instability strip (Byrne & Jeffery 2018;Romero et al 2018) associated with the iron opacity bump when metals are enhanced from radiative levitation. With this identification, these objects are less massive analogs of the BLAPs (Pietrukowicz et al 2017) which were also identified as He-core pre-WDs (Byrne & Jeffery 2018;Romero et al 2018). Though these new pulsators can potentially be explained by low-mass He-shell burning stars which have evolved off the extreme horizontal branch, the predicted periods from the MESA/GYRE models provide a better match with the He-core pre-WD models.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We have found a new class of radial mode pulsators (high-gravity-BLAPs) with T eff ≈ 30, 000 K that are consistent with ≈ 0.25 − 0.3 M ⊙ low-mass He-core pre-WDs transiting the newly identified instability strip (Byrne & Jeffery 2018;Romero et al 2018) associated with the iron opacity bump when metals are enhanced from radiative levitation. With this identification, these objects are less massive analogs of the BLAPs (Pietrukowicz et al 2017) which were also identified as He-core pre-WDs (Byrne & Jeffery 2018;Romero et al 2018). Though these new pulsators can potentially be explained by low-mass He-shell burning stars which have evolved off the extreme horizontal branch, the predicted periods from the MESA/GYRE models provide a better match with the He-core pre-WD models.…”
Section: Discussionsupporting
confidence: 67%
“…The large photometric amplitude, as well as the observed velocity and surface gravity shift, suggest that the observed pulsation modes are radial modes. Figure 7 in Byrne & Jeffery (2018) shows that unstable radial modes driven by the κ-mechanism due to the iron opacity bump are predicted for stars with our measured parameter when including radiative levitation. Our own initial non-adiabatic calculations agree with that result.…”
Section: Resultsmentioning
confidence: 75%
“…These authors have included the effects of radiative levitation which leads to mode excitation by the κ mechanism at T eff values comparable to those of BLAPs and the right period interval. By comparing with the observations, Byrne and Jeffery (2018) favor models with ∼ 0.31M ⊙ as the more likely candidates for BLAPs, in very good agreement with the scenario proposed by Romero et al (2018). Furthermore, and more importantly, the proposal of Romero et al (2018) that the Z bump (iron and nickel) in the opacity is responsible for the excitation of pulsations in BLAPs is confirmed by the more detailed radiative-levitation calculations carried out by Byrne and Jeffery (2018).…”
Section: Blue Large-amplitude Pulsators (Blaps)supporting
confidence: 69%
“…(1) progenitors of extremely low mass white dwarfs (Romero et al 2018) (2) post-common envelope stars (Byrne & Jeffery 2018, 2020; (3) mid/late stage of core helium burning stars (Wu & Li 2018). Ramsay (2018) applied interstellar reddening correction using data available from Gaia DR2 (Gaia Collaboration et al 2018) showing BLAPs occupying space near where hot subdwarfs and hot white dwarfs lie in the HR diagram.…”
Section: Introductionmentioning
confidence: 99%